Raman scattering in LiNiPO4 single crystal - Fomin, V. I.; Gnezdilov, V. P.; Kurnosov, V. S.; Peschanskii, A. V.; Yeremenko, A. V.; Schmid, H.; Rivera, J.-P.; Gentil, S. (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 2002)
The complete Raman spectra of a single crystal of LiNiPO4 for a wide temperature range are reported. Among the 36 Raman-active modes predicted by group theory, 33 have beendetected. The analysis of the spectra in terms of internal modes of the (PO4)3- group and of external modes is done with success. Besides, the multiphonon Raman scattering is discussed. Low-frequency lines, observed in the antiferromagnetic phase, are assigned to magnon scattering and are discussed briefly.